Evaluation of laboratory assays for anti‐platelet factor 4 antibodies after ChAdOx1 nCOV‐19 vaccination. (5th July 2021) - Platton, Sean; Bartlett, Andrew; MacCallum, Peter; Makris, Mike; McDonald, Vickie; Singh, Deepak; Scully, Marie; Pavord, Sue
Abstract: Introduction: Vaccine‐induced immune thrombocytopenia and thrombosis (VITT) following ChAdOx1 nCOV‐19 vaccine has been described, associated with unusual site thrombosis, thrombocytopenia, raised D‐dimer, and high‐titer immunoglobulin‐G (IgG) class anti‐platelet factor 4 (PF4) antibodies. Enzyme‐linked immunosorbent assays (ELISA) have been shown to detect anti‐PF4 in patients with VITT, but chemiluminescence assays do not reliably detect them. ELISA assays are not widely available in diagnostic laboratories, and, globally, very few laboratories perform platelet activation assays. Methods: Assays that are commercially available in the United Kingdom were evaluated for their ability to identify anti‐PF4 antibodies in samples from patients with suspected VITT. Four IgG‐specific ELISAs, two polyspecific ELISAs, and four rapid assays were performed on samples from 43 patients with suspected VITT from across the United Kingdom. Cases were identified after referral to the UK Expert Haematology Panel multidisciplinary team and categorized into unlikely, possible, or probable VITT. Results and Discussion: We demonstrated that the HemosIL AcuStar HIT‐IgG, HemosIL HIT‐Ab, Diamed PaGIA gel, and STic Expert assays have poor sensitivity for VITT in comparison to ELISA. Where these assays are used for heparin‐induced thrombocytopenia (HIT) diagnosis, laboratories should ensure that requests for suspected VITT are clearly identified so that an ELISA is performed. No superiority of IgG‐ELISAs over polyspecific ELISAs in sensitivity to VITT could be demonstrated. No single ELISA method detected all possible/probable VITT cases; if a single ELISA test is negative, a second ELISA or a platelet activation assay should be considered where there is strong clinical suspicion.